A case report of isolated lymphadenopathy revealing localized leishmanial lymphadenopathy in an asthenic 25-year-old man. Issue 29 (July 2016) - Hurlot, Quentin; Fillaux, Judith; Laurent, Camille; Berry, Antoine; Hofman, Paul; Marchou, Bruno; Delobel, Pierre; Brousset, Pierre; Martin-Blondel, Guillaume
Abstract: Background: Visceral leishmaniasis (VL) is endemic in large areas of the tropics, the subtropics, and the Mediterranean basin. Besides classical VL presentation, exceptional cases of a limited form of VL have been reported. Here we describe the challenges of diagnosis and management of this intriguing entity. Case summary: A 25-year-old French Caucasian man presented with marked asthenia that had lasted 6 months and was strictly isolated except for a 2-cm left cervical lymphadenopathy. The rest of the clinical examination and extensive biological exploration were unremarkable. Histological examination of the cervical lymphadenopathy showed a reactive lymphoid hyperplasia with granulomatous organization associated with small particles in the cytoplasm of epithelioid histiocytes and giant cells evocative of Leishman–Donovan bodies. Polymerase chain reaction (PCR) performed on the tissue confirmed the presence of Leishmania donovani/infantum DNA. Direct examination of a bone marrow aspiration, together with blood and bone marrow PCR, did not find other evidence for VL. Serology for leishmaniasis was unreactive. Extensive work-up for other causes of granulomatous lymphadenitis was negative. A diagnosis of localized leishmanial lymphadenopathy was made. Intravenous liposomal amphotericin B (20 mg/kg in five infusions) was initiated and well tolerated. Asthenia disappeared promptly and the patient fully recovered. Conclusion: Localized lymph node enlargement because of leishmanial infection should be included in the differential diagnosis of lymphadenopathy of unknown origin in patients who stayed or visited, even a long time ago and for a short period, endemic areas for leishmaniasis such as the Mediterranean basin. Fine-needle aspiration cytology and/or PCR for Leishmania sp of the lymphadenopathy might contribute to the diagnosis. A low-dose liposomal amphotericin B treatment might be effective, and deserves further study.